Speciation and preconcentration of vanadium(V) and vanadium(IV) in water samples by flow injection-inductively coupled plasma optical emission spectrometry and ultrasonic nebulization - Wuilloud, Rodolfo German (2001)
An on-line separation, preconcentration and determination system for vanadium(IV) and vanadium(V) comprising inductively coupled plasma optical emission spectrometry (ICP-OES) coupled to a flow injection (FI) method with an ultrasonic nebulization (USN) system was studied. The vanadium species were retained on an Amberlite XAD-7 resin as a vanadium-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (V-5-Br-PADAP) complex at pH 3.7. Enhanced selectivity was obtained with the combined use of the formation on-line of the complexes and 1,2-cyclohexanediaminetetraacetic acid (CDTA) as masking agent. The vanadium complexes were removed from the microcolumn with 25% v/v nitric acid. A sensitivity enhancement factor of 225 was obtained with respect to ICP-OES using pneumatic nebulization (15-fold for USN and 15-fold for the microcolumn). The detection limit for the preconcentration of 10 mL of aqueous solution was 19 ng L-1. The precision for 10 replicate determinations at the 5 μg L-1 V level was 2.3% relative standard deviation (RSD), calculated from the peak heights obtained. The calibration graph using the separation and preconcentration system for vanadium species was linear with a correlation coefficient of 0.9992 at levels from near the detection limits up to at least 100 μg L-1. The method was successfully applied to the speciation of vanadium in river water samples.